(241) عن تقييم المشروعات وتعيين أولوياتها - مصطفي الاروادي (معهد التخطيط القومى, 2026)
تتناول هذه المذكرة المنهجية العلمية لتقييم المشروعات وتحديد أولوياتها، حيث تفرق بين "التقييم الأولي" الذي تقوم به جهات التنفيذ بمنظور جزئي يركز على الربحية التجارية ومعايير مثل معدل العائد الداخلي وفترة الاسترداد، وبين "التقييم النهائي" الذي تضطلع به وزارة التخطيط بمنظور قومي شامل. ويهدف هذا التقييم الشامل إلى ضمان اتساق المشروعات مع استراتيجية التنمية طويلة الأجل، وتحقيق التكامل الفني والزمني بين مختلف القطاعات، بما يضمن تحويل الأهداف القومية الكلية المتعلقة بالدخل والعمالة إلى خطط تنفيذية متوازنة. كما تستعرض معايير المفاضلة والاختيار في ظل التخطيط المركزي، موضحاً وجود "مشروعات حتمية" تفرضها استراتيجية التنمية ولا تخضع للمفاضلة إلا في طرق تنفيذها التكنولوجية. وتدعو المذكرة إلى استخدام الأساليب الرياضية الحديثة مثل البرمجة الخطية للوصول إلى التشكيلة المثلى من المشروعات التي تحقق أقصى عائد بأقل موارد ممكنة، مشددة على أهمية التنسيق بين أجهزة التخطيط وجهات التنفيذ لتجنب تكرار الطاقات الإنتاجية غير المستغلة ومعالجة الاختلالات الهيكلية في الاقتصاد القومي. This memorandum addresses the scientific methodology for evaluating and prioritizing projects. It distinguishes between "initial evaluation," conducted by implementing bodies from a partial perspective focused on commercial profitability and criteria such as internal rate of return and payback period, and "final evaluation," undertaken by the Ministry of Planning from a comprehensive national perspective. This comprehensive evaluation aims to ensure that projects align with the long-term development strategy and achieve technical and temporal integration across different sectors, thereby guaranteeing the transformation of overall national objectives related to income and employment into balanced implementation plans. The memorandum also reviews the criteria for prioritization and selection under centralized planning, clarifying the existence of "mandatory projects" dictated by the development strategy, which are subject to prioritization only in terms of their technological implementation methods. The memorandum advocates for the use of modern mathematical methods, such as linear programming, to arrive at the optimal mix of projects that achieve maximum return with minimal resources. It emphasizes the importance of coordination between planning bodies and implementing agencies to avoid duplication of untapped production capacities and to address structural imbalances in the national economy.